Implementasi Metode Transformasi Biliniear Pada Filter Digital Infinite Impulse Response (IIR) Menggunakan Raspberry Pi - Murni Sri Rahayu Islamiyah; Rachmad Saptono; Hadiwiyatno Hadiwiyatno (Jurnal Jaringan Telekomunikasi, 2021)
The process of sending information there is always interference or noise, the nature of noise cannot be eliminated but can be minimized. In this study, the author uses an IIR Digital Filter because the IIR filter has an impulse of infinite duration so that it can be matched with an analog filter which also has an impulse response of infinite duration. 1 and chebyshev type 2 on MATLAB. MATLAB code is used to create a filter design program according to the specifications that have been made. MATLAB Simulink is used to create a block filter design to be implemented on the Raspberry Pi. Raspberry pi is used as a device to process the filter. The results of running MATLAB code and also Simulink are compared to see if the implementation results are the same as the program results. The types of filters that are good for use in IIR digital filters are Butterworth filters and Chebyshev 2 filters because there is no ripple in the passband. The type of filter that is not good for use in digital IIR filters is the Chebyshev 1 filter. The effect of ripple changes on the order value is that the smaller the ripple value, the larger the resulting order value. The effect of changing the stopband attenuation is that the more the stopband attenuation, the smaller the resulting order.